The Legal Certainty Surrounding the Status of Children Born Through in-Vitro Fertilization With a Deceased Biological Father is A Subject of Discussion - Dermawan, I Made (Sinergi International Journal of Law, 2024)
The purpose of marriage includes the desire to have offspring; however, not all married couples achieve this, often due to primary health issues. Expert doctors, armed with knowledge and technology, have discovered a method in the process of reproduction known as in-vitro fertilization (IVF). This discovery serves as a solution for married couples facing health problems. IVF is a process where egg fertilization by sperm occurs outside the female body, utilizing a fertilization tube. The resulting valid fertilization is then implanted in the wife's womb, from where the egg originated. The legal regulations for IVF are based on Law Number 36 of 2009 concerning health. Assisted pregnancy efforts can only be undertaken by legally married couples, meeting specific criteria such as fertilization materials originating from the husband and wife, with the implantation performed by authorized healthcare professionals at designated facilities. If these conditions are met, the offspring resulting from IVF is considered the biological child of the married couple. However, new challenges arise when the IVF process is conducted after the husband's demise, particularly in determining the lineage and civil rights status of the child or baby born through this process. To address these new challenges, this research aims to understand the legal status of posthumous IVF implementation and the lineage and civil rights status of children born through this process. The research is conducted through a literature review, utilizing a normative approach, with data collection from primary and secondary sources. The research findings indicate that the lineage and civil rights of a child born through posthumous IVF can be established with evidence from the biological father, demonstrated through scientific and technological means or other legal evidence establishing a blood relationship, as highlighted in Constitutional Court Decision No. 46/PUU VIII/2010.Keywords: In-Vitro Fertilization (Bayi Tabung), Legal Certainty, Civil Rights.